The The Literacy Building Strategy For Madrasah Branding At MA Darut Taqwa Pasuruan - Rizki Janata; Anita Puji Astutik (Sekolah Tinggi Agama Islam An-Nawawi Purworejo, 2021)
Madrasah is one of the educational institutions in Indonesia that played the role and responsibility in increasing the literacy of Indonesia's students. In Indonesia itself, the reading interest still needs more attention since it is still fragile. Expanding the reading interest for students in madrasah requires the proper strategies for effective results. MA Darut Taqwa is one of the madrasahs that commit to cultivating literacy among the students. The literacy program succeeded in increasing students' interest in reading and writing. Since that, the program has become the brand image of the madrasah itself. This study aims to describe the literacy for madrasah branding strategy implemented by MA Darut Taqwa to increase students' reading and writing skills. This study uses a qualitative descriptive approach to explain the branding strategy based on literacy in MA Darut Taqwa. The data validation technique used in this research is a triangulation of sources and methods. The research data was obtained through observations and interviews with the Head of Madrasah, Deputy Head of Curriculum and the Chair of the Literacy Drive Team as parties who have a significant role in realising the literacy madrasa branding. Many programs implemented by the madrasah to increasing students' reading and writing skills, such as writing classes, authorship workshops, comparative literacy studies and familiarising students with reading and writing for 30 minutes. The result of this strategy are students able to produce 15 books qualified by ISBN and make literacy a brand image that enhances the competitiveness of madrasah.